Ultracold atomic absorption imaging system in high magnetic fields - Chen, Yuying; Zhang, Zhengxi; Shui, Hongmian; Liang, Yun; Wei, Fansu; Zhou, Xiaoji (Chinese physics B, 2025)
Absorption imaging is a fundamental technique for quantitatively extracting information from ultracold atom experiments. Since ultracold 6 Li atoms are prepared and detected under high magnetic fields, the suitable detuning of the probe light can reach the GHz level compared to zero-field imaging. Therefore, based on the energy level structure of 6 Li atoms and the requirements of subsequent experiments, we design a high-field imaging system with a large frequency range and good robustness, starting from the rationality of the optical layout design and employing offset locking techniques. This imaging system covers the entire crossover region from Bose–Einstein condensate to Bardeen–Cooper–Schrieffer (BEC–BCS) and realizes free switching between zero-field and high-field imaging. Additionally, by introducing a proportionality coefficient to correct for the intensity fluctuations of the probe light, we mitigate its disturbance on the statistical measurement of particle numbers in the experiment. This work not only provides a design reference for other quantum gas experiments requiring absorption imaging under strong bias magnetic fields, but also serves as an important reference for improving the imaging performance.